Amination of phenylketenes. Substituent effect on amine‐catalyzed tautomerization of amide enol†. (10th July 2013) - Badal, Md. Mizanur Rahman; Zhang, Min; Kobayashi, Shinjiro; Mishima, Masaaki; Page, Michael I.
<x xml:space="preserve">Abstract</x> The transient intermediates with infrared bands at 1676–1680 cm−1 observed for reaction of substituted phenylketenes with diethylamine in acetonitrile were suggested to be the amide enols rather than the zwitterions on the basis of the theoretical calculations. A single broad band at 1674 cm−1 observed for reaction with the primary amines was attributed to overlap of two bands of the intermediate (amide enol) and the final product (amide). The substituent effect for the second‐order rate constants of diethylamine‐catalyzed tautomerization of the amide enol intermediates to give the amides was analyzed successfully by the Yukawa–Tsuno equation, giving a ρ value of 0.63 and an r− value of 1.31. The r− value larger than unity for pKa of phenols indicates that the negative charge formed at an oxygen atom of the amide enol at the transition state is significantly delocalized into the aromatic π‐system through the ethenyl group. This r− value was considered to reflect an intrinsic property of β‐phenylenolate skeleton. A remarkably small ρ value attributes to the cyclic transition structure where the negative charge disperses in a six‐member ring. Copyright © 2013 John Wiley & Sons, Ltd.